Cutaneous Granulocytic Sarcoma Concomitant to the Diagnosis of Acute Promyelocytic Leukemia - Feijó, Carolina Moreira (2022)
Introduction: Granulocytic sarcoma (GS) is a rare extramedullary tumor, made up by immature myeloid cells. It occurs in 2% to 14% of patients with acute myeloid leukemia (AML). The association with promyelocytic leukemia (APL) is even more rare, especially as manifestation at the time of diagnosis. The present study exposes the case of a patient with cutaneous GS concomitant with a diagnosis of APL. Case report: Male patient, 30 years old, referred to the Hematology Department due to fever, odynophagia, intense adynamia, hyporexia, loss of 5 kg, night sweating, in addition to progressive dyspnea over one month. Laboratory exams were run with evidence of severe anemia, proceeding to etiological investigation with myelogram, which showed 84% of blasts, and immunophenotyping compatible with promyelocytic leukemia (APL), PML-RARA positive (90%). Also, presented ulcerated lesions in the genital region and right leg, whose biopsy showed proliferation of suspected round cells for infiltration by AML/GS. Immunohistochemistry confirmed GS. The patient underwent chemotherapy, with good response to the treatment and improvement of blood counts. Skin lesions evolved with healing. After the 3rd consolidation, PML-RARA was negative. Conclusion: This case report describes a rare presentation of a malignant hematological disease, GS, also known as skin chloroma. A diagnostic strategy including images, histopathology, immunohistochemistry and laboratory tests were needed for confirmation. Timely diagnosis is essential, so that appropriate treatment is instituted soon, benefiting the patient regarding survival and quality of life.